Unique hemoglobin dynamics in female Tibetan highlanders - Hiroaki Arima; Masayuki Nakano; Sweta Koirala; Hiromu Ito; Basu Dev Pandey; Kishor Pandey; Takayuki Wada; Taro Yamamoto (Tropical Medicine and Health, 2021)
Abstract Background Tibetan highlanders have adapted to hypoxic environments through the development of unique mechanisms that suppress an increase in hemoglobin (Hb) concentration even in high-altitude areas. Hb concentrations generally decrease with increasing age. However, in the highlands, chronic altitude sickness is known to occur in the elderly population. To investigate how aging in a hypoxic environment affects Hb levels in Tibetan highlanders, we focused on the Mustang people, who live above 3500 m. We tried to clarify the pure relationship between aging and Hb levels in a hypoxic environment. Results We found that the Hb concentration increased with increasing age in females but not in males. Multivariate analysis showed that age, pulse pressure, the poverty index, and vascular diameter were strongly correlated with the Hb concentration. Conclusions We found unique Hb dynamics among female Tibetan highlanders. As seen in these Hb dynamics, there may be sex-based differences in the adaptive mechanism in Tibetan highlanders.